Temperature‐Induced Nonlinear Elastic Behavior in Berea Sandstone Explained by a Modified Sheared Contacts Model. Issue 1 (30th December 2022) - Simpson, Jonathan; van Wijk, Kasper; Adam, Ludmila; Esteban, Lionel
Abstract: Rocks commonly display a reduction in elastic modulus during an acoustic perturbation followed by a logarithmic recovery of the modulus to its original value. This nonlinear elastic behavior can also be induced by changes in temperature of the rock, although experimental data for this are sparse. In this paper, we utilize temperature perturbations to broaden our understanding of the causes and mechanisms of nonlinear elasticity in rocks. We perform laboratory experiments tracking the nonlinear response of a Berea sandstone under vacuum both during and following 10°C changes in temperature. Ultrasonic velocity decreases by up to 0.30 ± 0.02% during both temperature increases and decreases, before recovering in the following days. Continuous monitoring over a 2‐month period also reveals a longer‐term 0.78 ± 0.04% increase in velocity. To explain these observations, we modify a recent model for nonlinear elasticity based on the shearing and subsequent recreation of internal microscopic contacts. Application of this model to our data suggests that internal stresses from differential thermal expansion/contraction of mineral grains break contacts, inducing nonlinear weakening. The degree of weakening depends on the temperature gradient. Slow dynamics recovery in the ∼10 hr following a temperature change likely results from the recreation of broken contacts due to nanoscopic adhesive forces. In contrast, the long‐term velocity increase results from evaporation of bound water from clay minerals. In addition to furthering our understanding of nonlinear elasticity in rocks, our results imply that sudden changes of temperature in shallow crustal environments will induce nonlinear weakening that persists for hours to days. Plain Language Summary: Rocks weaken when seismic waves travel through them, a phenomenon which may drive critically stressed rocks to failure. This weakening is not permanent, however, and the rock recovers its original strength in the following minutes, hours, or days. Such behavior can also occur when the temperature of the rock changes, although only a handful of laboratory studies investigating this behavior exist. In this study, we monitor the speed of an ultrasonic wave (a proxy for strength) through a sample of Berea sandstone during and after temperature changes of 10°C. We find that whenever the temperature increases or decreases, the wave speed decreases by up to 0.30% before recovering to the original value in the following hours. By modifying a recently developed model, we find that this behavior is caused by microscopic bonds in the rock breaking and reforming during and after a temperature change. Additionally, an overall 0.78% increase in wave speed over 2 months is caused by water molecules evaporating from clay minerals. The results of our study help us to understand why rocks show this unusual behavior, and imply that a change in temperature in the earth will weaken nearby rocks for a period of time. Key Points: We monitor nonlinear reduction and recovery of ultrasonic velocity in Berea sandstone caused by 10°C changes in temperature Ultrasonic velocity drops by ∼0.3% for both temperature increases and decreases before recovering in the following days Our results and modeling emphasize that the rate of temperature change controls the magnitude of nonlinear weakening